(3WH GdabQGA hGdeSGcjfs - (3GHf GdLRGQ , CMeO Hf EHQGgje Hf CHj NGdO GdbjQhGfj, CHh LYaQ,J (B369 (3g` s
(3ChdgG (B:s
(3GeG HYO agPG GdcJGH ai PcQ GdWH , hYdGL GdLSe hGdfaS bGd GdeDda (B: (3Efj QCjJ cKjQoG ef YXeGA GdCWHGA hUahG cJHoG ai YdGL GdCOhGA s
(3BNQgG (B:s
(3UaI OhGA JVeO Hg GddKI GdOGejI Sha jLdh GdCSfGf hgh SYO hedM CfOQGfi hRHO GdHMQ , ef cd hGMO NeSI s
(3GdUaMI Gdhdi fGbUI hecedI HNW MOjK hHgGeT GdfSNI JYdjbGJs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B137s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B148 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1095s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs